A comparative evaluation of techniques of the removal of calcium hydroxide from root canals (Эндодонтия Today, 2020)
Preparations of calcium hydroxide have widely started to be used in endodontics since 1920. In domestic literature there are not enough data on quality of processing of root canals after temporary sealing by such preparations. In our research we suggest to use for removal of preparations of calcium hydroxide solution for drying and degreasing of root canals. The quality and quantitative evaluation of processing of root canals after temporary sealing by calcium hydroxide on the basis of the data radiological research and data of scanning electronic microscopy were conducted. The results obtained allow to recommend the use of a solution for drying and degreasing of the root canal to remove the drug Hydrol Metapex of the root canal.